Risk of Incident Chronic Obstructive Pulmonary Disease in Rheumatoid Arthritis: A Population‐Based Cohort Study. Issue 5 (2nd April 2018) - Mcguire, Katherine; Aviña‐Zubieta, J. Antonio; Esdaile, John M.; Sadatsafavi, Mohsen; Sayre, Eric C.; Abrahamowicz, Michal; Lacaille, Diane
Abstract : Objective: Studies have demonstrated a link between chronic obstructive pulmonary disease (COPD) and inflammation, raising the question whether chronic inflammatory conditions, such as rheumatoid arthritis (RA), predispose to COPD. Our objective was to evaluate the risk of incident COPD hospitalization in RA compared to the general population. Methods: We studied a population‐based incident RA cohort with matched general population controls, using administrative health data. All incident RA cases in British Columbia who first met RA definition between January 1996 and December 2006 were selected using previously published criteria. General population controls were randomly selected, matched 1:1 to RA cases on birth year, sex, and index year. COPD outcome was defined as hospitalization with a primary COPD code. Incidence rates, 95% confidence intervals (95% CIs), and incidence rate ratios (IRRs) were calculated for RA and controls. Multivariable Cox proportional hazards models estimated the risk of COPD in RA compared to the general population after adjusting for potential confounders. Sensitivity analyses were performed to test the robustness of the results to the possible confounding effect of smoking, unavailable in administrative data, and to COPD outcome definitions. Results: The cohorts included 24, 625 RA individuals and 25, 396 controls. The incidence of COPD hospitalization was greater in RA than controls (IRR 1.58, 95% CI 1.34–1.87). After adjusting for potential confounders, RA cases had a 47% greater risk of COPD hospitalization than controls. The increased risk remained significant after modeling for smoking and with varying COPD definitions. Conclusion: In our population‐based cohort, individuals with RA had a 47% greater risk of COPD hospitalization compared to the general population.